Expression and Isolation of N-Terminal Truncated Human Recombinant Renalase in Prokaryotic Cells - Fedchenko, V.I.; Kaloshin, A.A.; Kaloshina, S.A.; Medvedev, A.E. (Biomedical Chemistry: Research and Methods, 2021)
Renalase (RNLS) is a flavoproteinin which its N-terminal peptide (residues 1-17) has several important functions. In cells, it participates in the formation of the so-called Rossmanfold (residues 2-35), needed for «accommodation» of the FAD cofactor and for performing the catalytic functions of RNLS as a FAD-dependent oxidoreductase (EC 1.6.3.5). RNLS secretion into the extracellular space is accompanied by cleavage of this peptide. The resultant truncated extracellular RNLS cannot bind FAD and therefore performs various noncatalytic functions. In this work, we have performed expression the genetic construct encoding RNLS lacking its N-terminal signal peptide (tRNLS) in E. coli Rosetta (DE3) cells. The recombinant protein was accumulated in inclusion bodies in an insoluble form, which could be solubilized in the presence of a high concentration of urea or guanidine chloride. In contrast to full-length RNLS, which was effectively solubilized in the presence of 8 M urea, tRNLS was preferentially solubilized in the presence of 6 M guanidine chloride.